Membrane-Located Expression of Thioesterase From Acinetobacter baylyi Enhances Free Fatty Acid Production With Decreased Toxicity in Synechocystis sp. PCC6803 - Afrin, Shajia; Khan, Md. Rezaul Islam; Zhang, Weiyi; Wang, Yushu; Zhang, Weiwen; He, Lin; Ma, Gang (Frontiers in Microbiology, 2018)
It has been previously reported that photosynthetic production of extracellular free fatty acids (FFAs) in cyanobacteria was realized by thioesterases (TesA) mediated hydrolysis of fatty acyl-ACP in cytosol and excretion of the free fatty acid outside of the cell. However, two major issues related to the genetically modified strains need to be addressed before the scale-up commercial application becomes possible: namely, the toxicity of free fatty acids, and the diversity of carbon lengths of fatty acids that could mimic the fossil fuel. To address those issues, we hypothesized that generating FFAs near membrane could facilitate rapid excretion of the free fatty acid outside of the cell and thus decrease toxicity caused by intracellular FFAs in the cytosolic expression of thioesterase. To realize this, we localised a leaderless thioesterase (AcTesA) from Acinetobacter baylyi on the cytosolic side of the inner membrane of Synechocystis sp. PCC6803 using a membrane scaffolding system. The engineered strain with AcTesA on its membrane (mAcT) produced extracellular FFAs up to 171.9 ± 13.22 mg·L-1 compared with 40.24 ± 10.94 and 1.904 ± 0.158 mg·L-1 in the cytosol-expressed AcTesA (AcT) and wild-type (WT) strains, respectively. Moreover, the mAcT strain generated around 1.5 and 1.9 times less reactive oxygen species than AcT and WT, respectively. Approximately 78% of total FFAs were secreted with an average rate of 1 mg·L−1·h−1, which was higher than 0.44 mg·L−1·h−1 reported previously. In the case of mAcT strain, 60% of total secreted FFAs was monounsaturated (C18:1) which is the preferable biodiesel component. Therefore, the engineered mAcT strain shows enhanced FFAs production with less toxicity which is highly desirable for biodiesel production.